The Influence of Work Life Balance, Work Motivation and Dual Role Conflict on Employee Performance CV. Huda Jaya Sidoarjo - Aditiya Olanda; Ika Korika Swasti (Indonesian Journal of Business Analytics, 2023)
Economic difficulties are one of the driving factors that make housewives from low-income families work. Working can help them improve the fulfillment of family needs. This study aims to determine the influence of work-life balance, work motivation and conflict between multiple roles on the work performance of female employees at CV. Huda Jaya This study aims to determine the influence of work-life balance, work motivation and diverse role conflicts on the job performance of female employees at CV. Houda Jaya. Collecting data in this study using the method of distributing questionnaires and analysis using the Partial Least Square (PLS) application. The results of this study, namely that work-life balance, work motivation, and multiple role conflicts have a positive effect on employee performance CV. Huda Jaya Sidoarjo.